Causal Effects of an Ecologically Valid Home Numeracy Intervention on Preschoolers' Numeracy Skills. - Girard, Cléa; De Lamper, Angie; Callens, Stien; Van den Broek, Davina; De Smedt, Bert (Child Development)
The home numeracy environment is suggested to influence children's numerical development, but causal evidence for this assertion remains limited. Addressing this gap, we randomly assigned 117 predominantly White 4–5‐year‐olds (M = 4.68 years, SD = 0.2, 47% girls) attending preschool in Flanders (Belgium) to either an experimental (numeracy) or an active control (language) condition. The 6‐week intervention (pretest‐March 2023; posttest‐May 2023) consisted of an ecologically valid implementation, with parents integrating flexible activities into their routines. Pre‐ and post‐intervention assessments measured children's numerical skills. Medium effects were observed on transcoding and ordering skills, providing causal evidence for the impact of the home numeracy environment on children's numeracy. This study highlights the potential of ecologically valid interventions to support early numeracy in daily life.